PENGARUH VOLUME USAHA DAN HARGA POKOK PENJUALAN TERHADAP SISA HASIL USAHA - Kiki Nurohmah; Eris Darsawati; Acep Suherman (Jurnal Ilmu Akuntansi, 2022)
This study aims to determine the effect of business volume and cost of goods sold on the remaining operating results. The variables used in this study are business volume, cost of goods sold and the remaining operating results. This research was conducted at the Employee Cooperative of PT Sarandi in 2016 - 2021. The research method used was a quantitative method with an associative approach. The sampling technique used in this study is non-probability sampling with a total/census sampling technique. The data analysis used is parametric with multiple linear analysis. The results of the study of business volume have a positive effect on the remaining operating. Cost of goods sold has a negative effect on the remaining operating. And business volume and cost of goods sold have a simultaneous effect on the remaining operating. Therefore, the business volume and cost of goods sold need to be considered in cooperatives because they will affect the residual value of operating results.